2018
DOI: 10.1111/cfs.12444
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making in child welfare services: Professional discretion versus standardized templates

Abstract: The article explores differences in the assessment and decision‐making processes, in child welfare services where a standardized template is implemented and in services where it is not. Child welfare services in several countries use different approaches to assess children's and families' need for intervention. In Norway, as in other European countries, there is a shortage of knowledge about decision‐making strategies. The article examines how 36 child welfare caseworkers in 6 different teams in Norway investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Studies have identified different organisational factors that impact decision‐making, including work environment (Saltiel, 2016), organisational procedures (Broadhurst et al, 2010), organisational support (Falconer & Shardlow, 2018), decision support (Johnson et al, 2012; Lund, 2019), variation across organisations (Heggdalsvik et al, 2018; Johnson et al, 2012; Kjær & Mossige, 2013) and variation across nationalities (Križ & Skivness, 2013; Skiveness & Stenberg, 2015; Tefre, 2017).…”
Section: Decision‐making Ecology Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified different organisational factors that impact decision‐making, including work environment (Saltiel, 2016), organisational procedures (Broadhurst et al, 2010), organisational support (Falconer & Shardlow, 2018), decision support (Johnson et al, 2012; Lund, 2019), variation across organisations (Heggdalsvik et al, 2018; Johnson et al, 2012; Kjær & Mossige, 2013) and variation across nationalities (Križ & Skivness, 2013; Skiveness & Stenberg, 2015; Tefre, 2017).…”
Section: Decision‐making Ecology Themesmentioning
confidence: 99%
“…Inter-rater reliability testing among field staff showed high agreement rates for screening assessment items and the resulting decision, indicating a higher degree of consistency. In Norway, Heggdalsvik et al (2018) examined whether intake decision-making by social workers employed in agencies using a template differs from workers in agencies where decisions are based on discretion. The results show differences in reasoning, whether using a template or not (with more structured discussions vs. fragmented decisions emphasising emotions).…”
Section: Organisational Factorsmentioning
confidence: 99%
“…The CWS workers in the present study had concerns about being unable to discover and assess acute risks for children during the lockdown. Child welfare work involves acute assessments and standard procedures, with professional discretion playing a key role (Heggdalsvik et al, 2018;Munro, 2019;Samsonsen & Willumsen, 2014).…”
Section: Relational Child Welfare Work Under the Lockdownmentioning
confidence: 99%
“…At the same time, investigation takes place in a context of risksocial workers are expected to be thorough in their assessments in order to substantiate or invalidate concerns about risk of abuse or neglect. Our study of the management of complexity is anchored in two conceptual starting points: prioritising as an aspect of decision making (See for example: Britner and Mossler 2002;or Heggdalsvik, Rød, and Heggen 2018) and the wicked nature of social systems (Törnberg 2017). The first concerns prioritisation as an aspect of decision making in child welfare investigation.…”
Section: Prioritising and Wicked Problems In Child Welfarementioning
confidence: 99%